Implementation of State Defense Policies as an Effort to Strengthen Pancasila Values in the Millennial Generation - Rahmat Salam (Budapest International Research and Critics University, 2022)
Revolution 4.0 is marked by the development of information technology that is so fast and advanced that it significantly impacts people's lives, especially among millennials. Pancasila, as an ancestral heritage product that is extracted from the nation's cultural values, is significant in maintaining the existence of the Indonesian nation's personality, which at any time can be easily disturbed by various transnational ideologies that enter the community, especially among Millennials. Therefore, this study aims to determine the impact of implementing state defense policies to instill Pancasila values among the millennial generation. They have feelings of love for the homeland and awareness of the nation and state amid the massive development of information technology. This study uses a qualitative method with descriptive analysis. The study results show that the understanding of Pancasila values among the millennial generation is still shallow. Therefore it is necessary to strengthen Pancasila values through the State Defense policy. The State Defense policy itself for millennials is more directed at overcoming the notions, ideologies, and cultures that conflict with the personality values of the Indonesian people. The state defense policy as a reinforcement of Pancasila values among millennials can be carried out, among others, by maintaining security and order, such as being wise in using social media, complying with applicable laws and norms, serving the homeland following their respective fields, creating harmony, developing science and technology that is useful for the community, actively participates in positive activities, preserves the nation's culture and maintains the integrity of the nation's dignity.